Adopción de las normas internacionales de información financiera en la Cooperativa de Ahorro y Crédito Indígena Sac Latacunga ltda. de la provincia de Cotopaxi, cantón Latacunga período 01 de enero al 31 de diciembre de 2011 - Guaña Guano, Vilma Maribel (2015)
The present work is the development with the objective of carrying out the implementation of IFRS in the Credit Union Indigenous SAC Latacunga Ltda. because currently the institution does not perform with current regulations and presents your financial information with certain inconsistencies, however it necessary to regulate and standardize the presentation of financial information of the cooperative. The methodology used was the following: inductive-deductive method which allowed to learn theoretical and scientific, the analytic-synthetic method showing the current status of the entity it was also applied the techniques of observation, interview and survey whose results are analyzed and interpreted to improve the current situation of the cooperative….